STUDI LIVING HADIS TERHADAP PEMELIHARAAN ANJING OLEH KOMUNITAS PEBURU BABI KOTA PADANG - Wandi A (UIN Imam Bonjol Padang, 2018)
The tradition of hunting pigs with dogs has been evolving into a highlypopular form of sport hunting nowadays. The phenomenon of keeping dogs for hunting purposes by a community of Sports Association of Pig Hunting (PORBI) in Padang Panjang city raises the question whether their activity is in accordance with the context of living hadith and the provisions of authentic Islamic teachings, since this city is known as the city of ‘Veranda of Mecca’, where Islamic atmosphere can be easily seen in the city. The study found there were some reasons of the PORBI’s community to keep a dog in their house, such as keeping them for hunting purposes, strengthening the community relationship to one another, and the community who generally did not not know there were many Prophetic hadiths in which related with the keeping of dogs. The qualitative, field based approach was used as a research methodology and the data were exclusively sought from the PORBI's community. But alongside with this, the study suggests that a need for the PORBI’s community to increase their deep understanding of the Prophetic hadiths by referring to the syarah book of hadith. By doing so, it will give insight into their understanding of keeping the dogs as it is in accordance with the content of Prophetic hadiths.